EVALUATION OF USER EXPERIENCE OF MOBILE BANKING APPLICATIONS USING USER EXPERIENCE METHOD QUESTIONNAIRE (UEQ) AND HEURISTIC EVALUATION (HE) - Novianti, Elzy; Ahsyar, Tengku Khairil; Syaifullah, Syaifullah; Fronita, Mona (Informatika, Universitas Jenderal Soedirman, 2024)
One of the largest banks in Indonesia managed by the government is Bank Rakyat Indonesia. BRI is one of the banking institutions that implements a mobile banking system. Issues and disruptions in usability of the application, as indicated by survey results from users, have been identified. This research aims to evaluate the capability of the BRImo application to provide a positive user experience. In this research testing, two methods are applied: User Experience Questionnaire and Heuristic Evaluation. The results of the benchmark UEQ questionnaire testing show scores on the attractiveness scale at 1.61, efficiency at 1.76, and stimulation at 1.52, categorized as good, while scores from the perspicuity scale at 1.72, dependability at 1.48, and novelty at 0.75 are considered above average. Issues identified by experts with the BRImo application have the potential to hinder users. Based on the severity level testing results of 10 aspects of the method, Aesthetic and Minimalist Design received a rating of 2 (two), with a score of 1.66, indicating a need for improvement with low priority.